Selective recognition of bovine serum albumin (BSA) using molecular imprinting polymer technique - Mohd.Raflie, Maslih (2010)
The aim for this research is to produces protein separation tool by a new technique to separate protein molecule from protein solution.The technique used is the molecularly imprinted polymer,MIP.In this technique the target molecule that we want to separate will be the template and it mixed with selected monomers.Through polymerization process the template molecule will trapped between the polymer matrix that become solid and stable in term of heat and chemical. To make it has high selectivity on protein molecule the solid polymer is pounded to fine particles and through hydrolysis process the template is extracted and will leave complementary sequences that have exact configuration like the template shape.And further,two type of study were carried out, the first was analysis of particles structure in characterization of particles by using FT-IR spectrum and the second was study on the performances of this technique by conducting three experiments.The first experiment was the adsorption of BSA protein in MIP or synthesized polymer particles,the second experiment was the effect of protein concentration on separation and third experiment was to observe the effect of particles mass on separation. Polymerization and hydrolysis was successfully occur and it shown by the FT-IR spectrum.Experiment show that adsorption of protein was high for MIP particle that was 52.5 % while adsorption for NIP particle was 33.0 %.For the effect of concentration and mass of particle, it shows that the availability particle is the main factor that influence the amount of substrate separated